An Amphiphilic Pentaaryl Cyclopentadienyl Ruthenium(II) Molecular Rotor with a Luminescent Tag - Nishino, Toshio; Ohno, Yorie; Ishihara, Mika; Nishikawa, Yoshiko; Martin, Colin J.; Yasuhara, Kazuma; Rapenne, Gwénaël (Synlett, 2025)
This study presents a chemically modified molecular motor designed for interactions with lipid bilayers. By incorporating long alkyl chains into the anchoring fragment and a rhodamine luminescent tag onto the rotating subunit, we aimed to monitor the position of the motor and to permit its real-time visualization during membrane-perforation experiments. The synthesis of the functionalized tripodal ligand involved a seven-step process, culminating in the formation of a piano-stool Ru(II) complex that exhibits distinctive spectroscopic properties. The luminescence of the rhodamine tag, although slightly quenched upon incorporation in the Ru(II) complex, remains sufficiently strong to permit single-molecule observation using a total-internal-reflection fluorescence microscope.
Keywords: molecular rotors; ruthenium complexes; fluorescent tags; amphiphiles; membrane penetration